A MULTI-POINT MULTI-OBJECTIVE TRANSPORTATION ROUTE-OPTIMIZATION MODEL OF HAZARDOUS CHEMICALS - Li, Jingna; Wang, Jinghong; YOURAN ZHI; PAN, XUHAI (WIT Transactions on Engineering Sciences, 2018)
The transportation of dangerous goods/hazardous chemicals is a hot issue in the area of industrial safety. This paper investigates route optimization for the transportation of Adipic acid based on the fuzzy compromise approach and the iterative algorithm, proposing a multi-point multi-objective decision-making model of road transportation routing with minimum transportation risk, minimum transportation cost and minimum sensitive population. The three objective functions are integrated with weights by path optimization and risk decision model. The optimal compromised solution is obtained using the extended label correcting method. The iterative algorithm is used to remove the road section with maximum risk and get the final optimized route. The final optimized route is obtained by multiple optimizations, which combines the dual advantages of extended label correcting method and the iterative algorithm. Compared with the optimized route obtained by only using one-off optimization, the proposed method can consider the weight of the multi-objective functions to better balance the relationship among different objectives and is better to meet the requirement of the government, the transporters and the general public. An example is used to demonstrate the model. Using the route optimization model proposed in this paper, it is feasible to acquire a good balance between the risks and benefits associated with hazardous chemical transportation.